Transcutaneous auricular vagus nerve stimulation may benefit from the addition of N-acetylcysteine to facilitate motor learning in infants of diabetic mothers failing oral feeds - Jenkins, Dorothea D.; Garner, Sandra S.; Brennan, Alyssa; Morris, Jessica; Bonham, Kate; Adams, Lauren; Hunt, Sally; Moss, Hunter; Badran, Bashar W.; George, Mark S.; Wiest, Donald B. (Frontiers in Human Neuroscience, 2024)
Objective: To determine if pretreating with enteral N-acetylcysteine (NAC) improves CNS oxidative stress and facilitates improvement in oromotor skills during transcutaneous auricular nerve stimulation (taVNS) paired with oral feedings in infants of diabetic mothers (IDM) who are failing oral feeds. Methods: We treated 10 IDM who were gastrostomy tube candidates in an open-label trial of NAC and taVNS paired with oral feeding. NAC (75 or 100 mg/kg/dose) was given by nasogastric (NG) administration every 6h for 4 days, then combined with taVNS paired with 2 daily feeds for another 14d. NAC pharmacokinetic (PK) parameters were determined from plasma concentrations at baseline and at steady state on day 4 of treatment in conjunction with magnetic resonance spectroscopic (MRS) quantification of CNS glutathione (GSH) as a marker of oxidative stress. We compared increases in oral feeding volumes before and during taVNS treatment, and with a prior cohort of 12 IDM who largely failed to achieve full oral feeds with taVNS alone. Results: NAC 100mg/kg/dose every 6h NG resulted in plasma [NAC] that increased [GSH] in the basal ganglia a mean of 0.13±0.08mM (p=0.01, compared to baseline). Mean daily feeding volumes increased over 14d of NAC+taVNS compared with the 14d prior to treatment and compared with the prior cohort of 12 IDM treated with taVNS alone. Seven IDM reached full oral feeds sufficient for discharge, while three continued to have inadequate intake. Conclusions: In IDM failing oral feeds, NAC 100 mg/kg/dose every 6h NG for 4d prior to and during taVNS paired with oral feeding increased CNS GSH, potentially mitigating oxidative stress, and was associated with improving functional feeding outcomes compared with taVNS alone in a prior cohort. This represents a novel approach to neuromodulation and supports the concept that mitigation of ongoing oxidative stress may increase response to taVNS paired with a motor task.